SPRi-based hemagglutinin quantitative assay for influenza vaccine production monitoring. Issue 12 (14th March 2019) - Durous, Laurent; Julien, Thomas; Padey, Blandine; Traversier, Aurélien; Rosa-Calatrava, Manuel; Blum, Loïc J.; Marquette, Christophe A.; Petiot, Emma
Highlights: We report the development of an SPRi-based hemagglutinin quantitative assay. The assay enables vaccine potency evaluation and virus particles quantification. It presents higher reproducibility (<3%) and greater range (0.03–20 µg/ml) than SRID. SPRi-based assay offers good correlation with total viral particles counting. We used SPRi-based assay to monitor influenza production kinetics in cell culture. Abstract: Influenza vaccine manufacturers lack tools, whatever the involved production bioprocess (egg or cell-based), to precisely and accurately evaluate vaccine antigen content from samples. Indeed, the gold standard single-radial immunodiffusion (SRID) assay, which remains the only validated assay for the evaluation of influenza vaccine potency, is criticized by the scientific community and regulatory agencies since a decade for its high variability, lack of flexibility and low sensitivity. We hereby report an imaging surface plasmon resonance (SPRi) assay for the quantification of both inactivated vaccine influenza antigens and viral particles derived from egg- and cell-based production samples, respectively. The assay, based on fetuin-hemagglutinin interactions, presents higher reproducibility (<3%) and a greater analytical range (0.03–20 µg/mL) than SRID for bulk monovalent and trivalent vaccine and its limit of detection was evaluated to be 100 times lower than the SRID's one. Finally, viral particles production through cell culture-based bioprocess was also successfully monitored using our SPRi-based assay and a clear correlation was found between the biosensor response and total virus particle content.